Iron and nitrogen co-doping biochar for simultaneous and efficient adsorption of oxytetracycline and norfloxacin from wastewater - Cheng, Xiaoxue; Jiang, Ding; Zhu, Weiyi; Xu, Huan; Ling, Qifan; Yang, Jingwen; Wang, Xinyu; Zhang, Kexin; Zheng, Xiaolong; He, Sirong; Cao, Bin; Wagland, Stuart T.; et al. (Elsevier, 2025)
The global proliferation of antimicrobial resistance (AMR) poses a critical challenge to environmental and public health, driven by excessive antibiotic release from medical, agricultural, and aquaculture activities. This study investigates the synthesis and application of Fe/N-doped biochar derived from Enteromorpha clathrata (EC) for the removal of oxytetracycline (OTC) and norfloxacin (NOR) from water. The biochar, synthesized via pyrolysis and NaOH activation, was characterized by BET, SEM, and XPS analyses, revealing a porous structure with enriched functional groups. The EC-derived biochar demonstrated high adsorption capacities for OTC (625.325 mg·g⁻1) and NOR (487.379 mg·g⁻1) under neutral pH conditions, with adsorption following Langmuir and pseudo-second-order models, indicative of monolayer chemisorption. The biochar also exhibited excellent reusability, supporting practical applications. The strong interactions between the FeN4 active sites and the antibiotics were quantified through DFT calculations, showing binding energies of −394.91 kcal/mol for NOR and −398.10 kcal/mol for OTC, highlighting the important role of FeN4 in facilitating efficient adsorption. Additionally, density of states (DOS) analysis revealed that formation of Fe-N/O chemical bonds was confirmed through the hybridization of Fe 3d orbitals with N/O 2p orbitals. Overall, Fe/N-rich biochar contributes to its potential for practical applications in antibiotic removal from aqueous systems.
Keywords: Biochar; Antibiotic removal; Langmuir isotherm; Cooperative Chemisorption; pi-pi interactions; Orbital hybridization; 30 Agricultural, Veterinary and Food Sciences; 40 Engineering; 4004 Chemical Engineering; 3004 Crop and Pasture Production; 3006 Food Sciences; Biotechnology